Optimalisasi Local Taxing Power Berbasis Analisis Tax Effort Subnational: Studi pada Pemda di Provinsi Sulawesi Tenggara - Havidz Ibrahim; Dedi Purba; Furqan Furqan (Jurnal Manajemen Perbendaharaan, 2026)
One critical aspect of fiscal decentralization is the level of fiscal autonomy in each region, which refers to a region's ability to independently meet its financial needs. Most regencies and municipalities in Southeast Sulawesi Province are classified as having a very low level of fiscal autonomy. To date, evaluations of subnational tax performance have been heavily dominated by the tax ratio approach, which lacks accuracy in capturing actual regional capacity. Therefore, this study aims to provide strategy recommendations for enhancing local taxing power in the regencies and municipalities of Southeast Sulawesi based on their positions in the subnational tax effort quadrant to address these fiscal autonomy challenges. The research employs a mixed-methods approach using panel data from 17 regencies and municipalities spanning the 2019–2023 period. The quantitative analysis utilizes panel data regression to estimate tax capacity, while the qualitative analysis is grounded in the TADAT framework and triangulated interviews with local experts and regional stakeholders. The subnational tax effort quadrant is constructed based on the average tax ratio and tax effort of each regency and municipality across both mainland and island regions in Southeast Sulawesi Province. Tax effort is calculated as the ratio between realized local tax revenue and tax capacity, with tax capacity determined through a panel data regression model that incorporates variables such as per capita GRDP, workforce size, number of hotels, sectoral GRDP proportions, and capital expenditure, all of which are analyzed in relation to realized local tax revenue in each regency/municipality. These variables have been proven to significantly influence the realization of regional tax revenue. The results indicate that most regencies and municipalities in Southeast Sulawesi Province fall into Quadrant I, where both tax effort and tax ratio remain below average. It is recommended to enhance local taxing power through digitalization and tax administration reforms, risk-based supervision, compliance cost reduction, and tax awareness campaigns. The implication is that local governments must immediately shift from manual collection to an integrated digital platform and review the efficiency of fiscal incentives for National Strategic Projects to expand the local revenue base sustainably.